IMPROVING THE EFFICIENCY OF THE TECHNOLOGY FOR CLEANING SMALL IMPURITIES IN SEED COTTON (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article is about the national process of processing raw cotton with a variety of problems in cleaning large and small scum. In order to find solutions to this problem, it has been determined by the analysis of the effectiveness of the small-scale cotton-fertilization technology for other cotton fertilizers compared to other models